2018
DOI: 10.1152/physiolgenomics.00076.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of placental growth factor deficiency on behavior, neuroanatomy, and cerebrovasculature of mice

Abstract: Preeclampsia, a hypertensive syndrome occurring in 3-5% of human pregnancies, has lifelong health consequences for fetuses. Cognitive ability throughout life is altered, and adult stroke risk is increased. One potential etiological factor for altered brain development is low concentrations of proangiogenic placental growth factor (PGF). Impaired PGF production may promote an antiangiogenic fetal environment during neural and cerebrovascular development. We previously reported delayed vascularization of the hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 85 publications
(105 reference statements)
0
21
0
Order By: Relevance
“…Despite methodological differences, both our work and previous studies demonstrate that chronically increased maternal vasopressin is sufficient to cause sustained and significant changes to offspring brain function. Changes to anxiety and memory-related behaviors have also been noted in other animal models of preeclampsia, including the L-NAME treatment 36,37 and PlGF deficiency models 38,39 . Here, we have expanded upon prior findings by also addressing potential neuromolecular and neurocellular changes in this model-sex-specific abnormalities in cortical and subcortical growth, and synaptic protein distribution, as well as embryonic brain transcriptomics.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Despite methodological differences, both our work and previous studies demonstrate that chronically increased maternal vasopressin is sufficient to cause sustained and significant changes to offspring brain function. Changes to anxiety and memory-related behaviors have also been noted in other animal models of preeclampsia, including the L-NAME treatment 36,37 and PlGF deficiency models 38,39 . Here, we have expanded upon prior findings by also addressing potential neuromolecular and neurocellular changes in this model-sex-specific abnormalities in cortical and subcortical growth, and synaptic protein distribution, as well as embryonic brain transcriptomics.…”
Section: Discussionmentioning
confidence: 78%
“…The PlGF deficiency and L-NAME treatment models both specifically exhibited abnormal spatial memory 37,38 , coupled in the latter case with altered hippocampal neurogenesis 36 . Collectively, this work suggests common disruptions to memory neurocircuitry, as demonstrated by abnormal behavior and hippocampal synaptic densities in AVP-exposed female offspring here.…”
Section: Discussionmentioning
confidence: 99%
“…While the resistance in an individual capillary is quite high, when there is a dense capillary bed with several small vessels running parallel to one another, vascular resistance drops (Mandeville and Rosen, 2002). It is therefore possible that if the offspring in our study also experienced altered angiogenesis as seen in the PGF model (Kay et al, 2018), then global cerebral vascular resistance could be decreased, thus providing an explanation for the observed increased perfusion in response to whisker stimulation compared to control offspring. In a hypertensive environment, cerebral vessels are remodeled to protect against sudden spikes in blood pressure, however this could impair their general function at lower blood pressures (Jones-Muhammad and Warrington, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…One link worth further exploring between altered cerebrovascular and behavioral function in offspring of preeclamptic mothers stems from the fact that levels of placental growth factor (PGF) were markedly low during a preeclamptic pregnancy. One group has used PGF knockout mice as a preclinical model for offspring of preeclamptic mothers and found working memory deficits along with increased vascular density and length at the capillary level, without any changes in cerebral blood volume (Kay et al, 2018). Furthermore, when challenged with a common carotid artery ligation, CBF was lower in the PGF knockout mice, as measured by laser Doppler flowmetry (Luna et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An increased level of sFlt-1 binds to VEGF and PlGF, which are important angiogenesis and vasculogenesis factors, resulting in endothelial dysfunction in various organs, including the kidney ( 48 ). A recent study demonstrated the effects of PlGF deficiency on the behavior, neuroanatomy, and cerebrovasculature of mice ( 49 ).…”
Section: Discussionmentioning
confidence: 99%